Economic and Environmental Marketing in Establishment of Tourist Territories. Exemplified by the Republic of Altai - KUTTUBAEVA, Toskanaj Ajtmukanovna; ISHHUK, Ljudmila Viktorovna; GLOTKO, Andrej Vladimirovich; CHERNOVA, Evgenija Olegovna; SUHOVA, Marija Gennad'evna (Journal of Environmental Management and Tourism; Vol 9 No 2 (2018): JEMT Volume IX Issue 2(26) Spring 2018DO - 10.14505//jemt.9.2(26).19, 2018)
The ecological and economic preconditions for the tourist development of the Republic of Altai are considered in this article. The cultural-historical, socio-economic and infrastructure resources and conditions are assessed in terms of accessibility, quality and completeness of the spectrum. The data are illustrated by the chart and the diagram. The strengths and weaknesses of each component of the tourist potential of the Republic of Altai are analyzed. The results of the analysis are presented in the succinct tabular form. The tourist specialization is defined for each administrative district of the republic and the recommendations for further development are given. In the study, the authors express the measures required in their opinion to activate the development of rural and therapeutic-resort types of tourism. The republic is also interesting from the point of view of ethnography, which is also given attention herein. However, the territory with rich natural, cultural-historical resources and a developed infrastructure may remain at the level of prospects without a proper marketing strategy. Therefore, much attention is paid to the marketing strategy. The successful communication policy should cover several areas, which are discussed in detail herein. Based on the experience and recommendations of this study, it is possible to build a literate and effective way for the establishment of tourist territories in the Republic of Altai.